2014
DOI: 10.3126/jcmsn.v9i2.9683
|View full text |Cite
|
Sign up to set email alerts
|

Study of endometrial Status of Patients with Abnormal Uterine Bleeding in Patan Hospital

Abstract: BackgroundAbnormal uterine bleeding may be defined as changes in frequency of menstruation, duration of flow or amount of blood loss. Early accurate diagnosis and proper treatment is essential to prevent progress to endometrial cancer. ObjectiveThis study was done to evaluate the histopathology of endometrium for identifying the endometrial causes of abnormal uterine bleeding. MethodThis was a retrospective study done in department of pathology, Patan Hospital from 1 August 2011-to 31 July 2012; total 413 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…All the cases were categorized into reproductive (15-40 years), perimenopausal (41-50 years) and postmenopausal (>50 years) groups; done in accordance to studies by several authors. 3,10,11 There were 226 patients belonging to the reproductive age group (21-40 years). Proliferative endometrium was the dominant histological finding in this age group accounting for 51.8% followed by 32.3% of secretory endometrium; there were no cases of malignancy in this group.…”
Section: Analysis Of Histopathological Findingsmentioning
confidence: 99%
“…All the cases were categorized into reproductive (15-40 years), perimenopausal (41-50 years) and postmenopausal (>50 years) groups; done in accordance to studies by several authors. 3,10,11 There were 226 patients belonging to the reproductive age group (21-40 years). Proliferative endometrium was the dominant histological finding in this age group accounting for 51.8% followed by 32.3% of secretory endometrium; there were no cases of malignancy in this group.…”
Section: Analysis Of Histopathological Findingsmentioning
confidence: 99%
“…Shrestha et al also showed that endometrial carcinoma is most commonly found in postmenopausal age group. 11 So, histopathological diagnosis of endometrium in AUB patients is an important and a necessary investigation for appropriate planning of optimal treatment in these patients and to prevent the development of endometrial carcinoma. 12 AUB in perimenopausal and postmenopausal patients is alarming and needs meticulous evaluation because it could be the only clinical symptom of endometrial carcinoma and preneoplastic conditions in these patients.…”
Section: Discussionmentioning
confidence: 99%